(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article presents a comprehensive analysis of modern technologies in pediatric neurosurgery, demonstrating revolutionary changes in diagnosis, surgical treatment and patient rehabilitation. The material is of interest to specialists in neurosurgery, paediatrics and medical technologies.